Cochleopalpebral reflex: sensitivity and specificity in the auditory screening of newborns discharged from the neonatal intensive care unit - Carlos F. Martínez Cruz; Mayra N. Ramírez-Vargas; Martina A. Guido-Campuzano; Patricia García- (Permanyer, 2021)
Background: The sensitivity and specificity of the clinical audiological evaluation in newborns are debatable compared to neurophysiological methods of a hearing evaluation. This study aimed to determine the sensitivity and specificity of the cochleopalpebral reflex as a clinical test for hearing screening in newborns. Methods: A case-control study was designed. Newborns discharged from a neonatal intensive care unit (NICU) were included. Brainstem evoked auditory potentials were recorded. A wooden rattle was used to explore the cochleopalpebral reflex. The sensitivity and specificity of the cochleopalpebral reflex were calculated. Continuous data were analyzed with Student's t-test, with statistically significant p-values < 0.05. Results: We selected 450 newborns who were divided into two groups: group A, with bilateral sensory neural hearing loss (n = 150), and group B, with normal hearing (n = 300). Group A showed a significantly lower gestation age at birth (p = 0.005) compared to group B (32.5 ± 2.6 vs. 34.4 ± 3.5 weeks). In group A, the cochleopalpebral reflex's sensitivity was 80% using the wooden rattle. In group B, the specificity was 98%. Conclusions: The NICU discharged newborns' clinical hearing evaluation is not enough to exclude hearing loss. Although it may be the only diagnostic tool for hearing loss in some settings, its limitations should be considered.